2009
DOI: 10.1111/j.1467-7717.2009.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Framework for integrating indigenous and scientific knowledge for disaster risk reduction

Abstract: A growing awareness of the value of indigenous knowledge has prompted calls for its use within disaster risk reduction. The use of indigenous knowledge alongside scientific knowledge is increasingly advocated but there is as yet no clearly developed framework demonstrating how the two may be integrated to reduce community vulnerability to environmental hazards. This paper presents such a framework, using a participatory approach in which relevant indigenous and scientific knowledge may be integrated to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
239
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(268 citation statements)
references
References 54 publications
5
239
0
4
Order By: Relevance
“…This study has highlighted the importance of indigenous knowledge and its value in engaging peripheral communities in developing countries in disaster risk management, which is being increasingly acknowledged as central to development agendas (Mercer et al 2007;Mercer et al 2010). .…”
Section: Discussionmentioning
confidence: 99%
“…This study has highlighted the importance of indigenous knowledge and its value in engaging peripheral communities in developing countries in disaster risk management, which is being increasingly acknowledged as central to development agendas (Mercer et al 2007;Mercer et al 2010). .…”
Section: Discussionmentioning
confidence: 99%
“…A influência desse grupo de pesquisa se exprime na instituição e controle do Research Committee on Sociology of Disasters rc39 da isa, e do principal periódico o International Journal of Mass Emergencies and Disasters. Porém, apesar das diferenças, os desastres nos países do Terceiro Mundo são pesquisados por esses sociólogos sem referências aos autores da região (Kreps, 1995;Wisner, 1994) ou, mesmo quando as concepções locais são consideradas, elas são feitas por porta-vozes centrais (Mercer et al, 2010).…”
Section: Quadro 2 Formação Do Campo Disciplinarunclassified
“…Nesse sentido, verifica-se o reconhecimento dos mecanismos existentes de enfrentamento e das capacidades da comunidade/pessoas, bem como do know-how e dos recursos locais para estabelecer estratégias e planos de redução de risco de desastre, priorizando a participação dos grupos mais vulneráveis. Esse reconhecimento exprime a crescente conscientização do valor do conhecimento prático como, por exemplo, a associação do conhecimento tradicional e indígena ao conhecimento científico na redução do risco de desastres (Mercer et al, 2010).…”
Section: A Controvérsia Extradisciplina: a Oposição Recuperação-prepaunclassified
“…Previous research has suggested the integration of specific traditional coping strategies or adaptations into CCA (Mercer et al 2010). CCA frameworks should consider the cultural dimensions that underlie adaptations, and in the case of the Peruvian Andes, how these form part of the unified holistic cosmo-vision.…”
Section: Cultural Dynamic Of Adaptationmentioning
confidence: 99%
“…In reality many indigenous groups have shown themselves to be highly attuned to changes in the environment and have developed a suite of practices in response (Salick and Byg 2007). These practices are often referred to as "traditional knowledge" and are increasingly being accepted as a potential contributor to the management of climate change (Mercer et al 2010). However, as Briggs (2005) argues, much of the research examining traditional knowledge represents empirical or "(arte)factual" evidence of specific coping strategies in communities, instead of a deeper understanding of the epistemology of knowledge within culture.…”
Section: Ayni Ayllu Yanantin and Chaninchamentioning
confidence: 99%